2017
DOI: 10.1016/j.jid.2017.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Sulfate Promotes IL-17A Producing CD4+ T Cells by an IL-23-Dependent Mechanism Regulated by TLR4 and Jak-STAT Pathways

Abstract: Allergic contact dermatitis, caused by nickel, is a delayed-type hypersensitivity reaction, and 14.5% of the general population may be affected in Europe. Among a wide range of cytokines, the IL-12 family has unique structural and immunological characteristics. Whereas IL-12p70 promotes T helper (Th) 1 cell polarization, IL-23 promotes Th17 cell development and both have been isolated from nickel-allergic patients. In this work, we were interested in understanding the mechanism behind nickel-induced Th17 cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 44 publications
(60 reference statements)
7
30
0
Order By: Relevance
“…Bechara et al . found that exposure to nickel in human monocyte‐derived dendritic cells leads to an upregulation of IL‐23, and this cytokine has an important role in the development of Th17 cells and the production of IL‐17A, which is in line with the results of a previous study .…”
Section: Results Of Patch Test Scoring and Grade Of Inflammation In Ssupporting
confidence: 85%
“…Bechara et al . found that exposure to nickel in human monocyte‐derived dendritic cells leads to an upregulation of IL‐23, and this cytokine has an important role in the development of Th17 cells and the production of IL‐17A, which is in line with the results of a previous study .…”
Section: Results Of Patch Test Scoring and Grade Of Inflammation In Ssupporting
confidence: 85%
“…This illustrates another strength of this test as there is often a significant delay between exposure and diagnostic work‐up. Our study confirms previous findings by us and others that CD4 + cells are the dominant proliferating population and thereby also verifies a cell‐mediated hypersensitivity reaction 7,31‐33 . Furthermore, by discriminating CD4 + from CD8 + cells, higher SI’s and better diagnostic values could be found.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous reports also demonstrated activation of MAPKs and NF-kB subunit p65 in moDC in response to danger signals such as lipopolysaccharide and contact sensitizers, such as nickel. 14,16,19 We were then interested in the upstream signaling pathways that participated in DC response to hGH aggregates. Both Rac1 and PI3K are highly involved in actin remodeling observed in phagocytosis, the internalization mechanism of large insoluble particles by innate immune cells such as macrophages, neutrophils, and dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors concentrations and treatment timelines were optimized to avoid cellular toxicity, according to previous studies. 16 Results showed that cxcl10 expression was decreased when moDCs were pretreated with these inhibitors, suggesting that hGH aggregates modulate cxcl10 expression via NF-kB, ERK, JNK, and p38 MAPK signaling pathways (Fig. 3a).…”
Section: Hgh Aggregates Regulate Cxcl10 Mrna Expression Via Mapk and mentioning
confidence: 93%